Implementation of Local Government Information System (SIPD) And Human Resources Quality on the Financial Performance of PPKBPPPA Service of Garut Regency - Taryan Kusnara; Mulyaningsih, Mulyaningsih; Gugun Geusan Akbar; Irfan, Irfan; Yagus, Yagus (SEAN Institute, 2024)
This research aims to analyze the impact of the implementation of the Regional Government Information System (SIPD) and the quality of human resources (HR) on financial performance at the PPKBPPPA Office of Garut Regency. This study uses a quantitative method with regression analysis. The results of the study indicate that the implementation of SIPD has a significant effect on financial performance with a regression coefficient of 0.652 and a significance of 0.000 (p <0.05). The quality of HR also has a significant effect with a regression coefficient of 0.578 and a significance of 0.001 (p <0.05). Simultaneously, both variables have a greater influence with an R-squared value of 0.765. This shows that improving financial performance does not only depend on the system, but also on the quality of HR. Therefore, a policy is needed that balances technological improvements and HR development so that financial management is more efficient, transparent, and accountable. This study has implications that improving financial performance in the local government environment does not only depend on the use of the latest technology systems, but also on the quality of HR running the system. Therefore, a policy is needed that is oriented towards a balance between strengthening technological infrastructure and increasing employee capacity, so that the implementation of SIPD can run more optimally and contribute to more accountable and transparent financial governance.